FUNCTIONS OF HIGHER PROFESSIONAL FOREIGN LANGUAGE EDUCATION - M. A. Bogatyreova (Vestnik MGIMO-Universiteta)
The article is about the functions of professional higher education dealing with the sphere of foreign languages (FL). There are all indications that these functions are mainly determined by the higher education objectives, the dominating role that foreign languages play in modern society and politics. The analysis of existing linguistic concepts (up to the ХХ-th century) as well as the current state of FL educational system, testifies to the fact that a number of urgent and indispensable changes are needed. The desirable transformations are aimed to amplify the contents of the functional burden of professional FL education. According to the provisions of the latest state standards, the transmission to new paradigms of thinking is primarily provided by the innovation modus, that is intended to steadily develop sociocultural technologies, improve the contents of FL education, increase the effectiveness of students' achievements, work out a new system of monitoring, controlling and assessing academic results. However, multi-media techniques and strategies should be associated with the anthropological paradigm, capable of driving in motion the "front-running" mechanism of sociocultural reproduction. That means that graduates' FL proficiency, alongside with influence, property and benefit, is becoming the most important indicator of social status in modern society. Consequently, multifunctional FL education is supposed to reflect the formation of axiological values of students, their inner motives and personal attitudes that, being embodied in the creative products of speech, exercise an essential impact on valuable society orientations. Evidently, society is intellectual to an extent it applies knowledge which was accumulated in the cultural gene pool of humanity. It is just through the educational channel that the basic value of culture performs the function of adjusting objective reality to individuals' goals and their meaningful implications. The language conjures a subjective image of the objective world, and in the context of individual approach it does not only mean building one's own trajectory of covering the academic material, but also developing strategies of transforming the world. According to the culture-centred principle, which underlies educational functions, the latter tend to unfold logically in any separate classification of functions.